Unveiling vital biomarkers and immune infiltration profiles in endoplasmic reticulum stress following spinal cord injury - Yunpeng Zhang; Xiaoming Tang; Jian Dai; Yao Li; Jian Ma (Scientific Reports)
Abstract Spinal cord injury (SCI) is a profound affliction of the central nervous system that often remains inadequately addressed. Prior research has indicated that endoplasmic reticulum stress (ERS), associated with apoptotic signaling, plays a part in subsequent injuries post-SCI. However, the exact mechanisms are still unclear. ERS-related genes and SCI-associated datasets were sourced from the Genecard and GEO databases. We identified 68 ERSDEGs and pinpointed 6 marker genes vital for SCI diagnosis (CYBB, PRDX6, PTGS1, GCH1, TLR2 and PIK3CG) which were all upregulated in SCI based on bioinformatics and qRT-PCR. The nomogram exhibited that these genes could effectively predict the occurrence of SCI. Functional analysis revealed the potential roles of these genes was closely related to neuron cells and immune response. Immune infiltration research underscored the substantial roles of macrophage and CD56 dim NK cells in SCI. The ceRNA network analysis further revealed the complex interplay among marker genes, lncRNAs and miRNAs in SCI. We screened six marker genes with great diagnostic value, and found that these genes may affect the occurrence of SCI by affecting the immune response and recovery of neurons.